Going bicoastal - Adler, Dahlia (Wednesday Books, 2023)
Told in alternating timelines, Jewish seventeen-year-old Natalya spends one summer in New York with her dad, trying to muster the courage to talk to her girl crush, and the other in Los Angeles with her estranged mom, going for a guy she never saw coming.